The Cytology, Isozyme, HPLC Fingerprint, and Interspecific Hybridization Studies of Genus Epimedium (Berberidaceae). (19th November 2013) - Wang, Lin-Jiao; Sheng, Mao-Yin
Abstract : 104 samples from 27 accessions belonging to 12 species of genus Epimedium were studied on the basis of cytology observation, POD (i.e., peroxide) isozyme, high performance liquid chromatography (i.e., HPLC) fingerprint, and interspecific hybridization. The cytology observation showed karyotypes of twelve species studied; all are 2A symmetry type of Stebbins standard and similar to each other, and except for karyotype of E. leptorrhizum which is 2n = 2x = 8m (2SAT) + 4sm, the rest are 2n = 2x = 6m (2SAT) + 6sm. Chromosomes C-banding of barrenwort species varies, with 15 to 22 bands, consisting of centromeric bands, intercalary bands, terminal bands, and middle satellite bands. Results of POD isozyme showed that the zymographs vary greatly and sixteen bands were detected in the eleven species, and each species has its own characteristic bands different from the others. Studies on the HPLC fingerprint showed that the HPLC fingerprint of different species has characteristic peaks, divided into two regions (retention time < 10 min and retention time > 10 min). Results of interspecific hybridization showed that crosses of any combination among seven species studied are successful and the rates of grain set vary greatly. Based on these results, the system and phylogeny of this genus were inferred.